WALKING/SURVIVING IN THE FOREIGN LAND: RECONSIDERING JAMAICA KINCAID’S LUCY - Tang-Wei, Wang (PEOPLE: International Journal of Social Sciences, 2017)
In her most admired novella, Lucy, Jamaica Kincaid deploys a diasporic narrative to re-consider the atrocious British colonial ideology, on the one hand, and to level against the first world woman discourse, on the other. Set in 1969, the novel manifests how the Mariah’s first woman discourse places the heroine in the dilemma of assimilation and resistance; nevertheless, it confirms Lucy’s politics of location. Drawing on Frantz Fanon’s insight into colonialism—particularly his analysis of atrocious colonialism in erasing the subjectivity of the colonized—this paper, first of all, argues that Mariah’s white woman discourse is thinly disguised colonialism which distorts Lucy’s conception with her whiteness. Moreover, this paper employs contemporary discourses on the politics of differences to argue that: first, Lucy’s identity is constructed around the coercive colonial ideology apparatus—the atrocity of which causes tremendous trauma—and is meanwhile predicated on the difference between her and Mariah. Secondly, Mariah’s hospitality and generosity dissipating the difference of black women should be perceived as an alternative “gaze of the colonizer.” Thirdly, Lucy’s divergent identity cannot be totalized by any essentialism and her becomingness deconstructs any essentialist understanding of cultural identity. As an immigrant who is from Antiqua, Lucy’s ethnicity offers her a lens to counteract Mariah’s generosity and hospitality narcissistic and to detach herself from Mariah’s white universalism. In conclusion, the dialectics of Lucy and Mariah embedded in his novel bespeaks well the contingency of self-reflection on cultural identity. Thus, this paper will assert that Kincaid’s Lucy epitomizes the black diaspora’s “politics of location.”